Standard Operating Procedure (SOP) Upaya Peningkatan Mutu Layanan Perpustakaan Sekolah Tinggi Agama Islam Negeri (STAIN) Ponorogo - Kardi Kardi (Pustakaloka, 2010)
To achieve good governance, library need an integrated quality control of allits elements. Consequently, the quality manual device for library activities is needed. Quality manual is a coordinated activities to direct, control and organize so that the quality or performance of library standard can be achieved. Quality manual is basically a concise statement of policies, objectives, and key processes. Library standard Operating Procedure (SOP) is part of quality standards  developed by the library. in general, preparation of SOP includes four steps, i.e. needs analysis, SOP, SOP development, SOP implementation, monitoring and evaluation. Therefore, it can procedure SOP concistenly appropriate to the needs to support the completeness of the integrated quality management in the libraries.